ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - SE., M.Si, Ak, Murtini,; Hidayah, SE., Ak, Rini; Ariyanti, SE, Yuni (Majalah Neraca, 2013)
This research aims to know empirical evidence as for factors influencing timeliness of financial reporting of manufacture firm listed in Indonesia Stock Exchange. The factors to be analysised in this research are profitability, reputation of public accountant, ownership structure, auditor opinion, firms size, and firms age.Â Sample of this research is 72 manufacture firms listed in Indonesia Stock exchange period 2008-2011 that selected by using purposive sampling method. Technique of analysis for examining the hipotesis was logistic logistic regression at level significance 5 percent.The result of this research provides evidence that profitability have influence on by significance to timeliness of financial reporting. However there is no evidence that reputation of public accountant, ownership structure, auditor opinion, firms size, and firms age have influence on timeliness of financial reporting of manufacture firm listed in Indonesia Stock exchange.Keywords : timeliness, profitability, reputation of public accountant, ownership structure, auditor opinion, firms size, and firms age.